2005
DOI: 10.1080/10556780500140664
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of symmetric composition constants for symmetric integrators

Abstract: This work focuses on the derivation of composition methods for the numerical integration of ordinary differential equations, which give rise to very challenging optimization problems. Composition is a useful technique for constructing high order approximations, while conserving certain geometric properties. We survey existing composition methods and describe results of an intensive numerical search for new methods. Details of the search procedure are given along with numerical examples, which indicate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 24 publications
0
68
0
Order By: Relevance
“…The coefficients used in those integrators are the ones found by McLachlan (1995) and McLachlan et al (2002). The 6th order integrators implemented in AMUSE are of 11 and 13 stages (M11 and M13), with the coefficients found by Sofroniou & Spaletta (2005). In the simulations performed here, we used the Rotating Bridge with a 6th order integrator.…”
Section: A1 High Order Integratorsmentioning
confidence: 99%
“…The coefficients used in those integrators are the ones found by McLachlan (1995) and McLachlan et al (2002). The 6th order integrators implemented in AMUSE are of 11 and 13 stages (M11 and M13), with the coefficients found by Sofroniou & Spaletta (2005). In the simulations performed here, we used the Rotating Bridge with a 6th order integrator.…”
Section: A1 High Order Integratorsmentioning
confidence: 99%
“…However, I recommend an implementation following that of Bader and Deuflhard [1,5]. Using the Mathematica's NDSolve framework developed by Sofroniou et al [18,19], the current state of the art implementation of each of the methods presented in this paper requires only a few lines of Mathematica code. This author has shown that such implementation may solve all the ODE problems in the Test Set of IVP Solvers at Bari, Italy (formerly at CWI, Amsterdam) [15], including those derived from partial differential equations (PDE) by the method of lines.…”
Section: Appendix A: Practical Implementation Of Non-linear One-step mentioning
confidence: 99%
“…3, we compare some well known higher order integrators with the PV-based, minimal extrapolated integrators (17). KL8 and SS10 are eighth and tenth order symplectic integrators by Kahan and Li (1997) and Sofroniou and Spaletta (2005) with 17 and 35 force evaluations, respectively. Both are recommended by Hairer et al (2002).…”
Section: Higher Order Comparisonsmentioning
confidence: 99%